2022
DOI: 10.1002/cctc.202200043
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐ and Enantioselective Photoenzymatic Ketone Reductions Using a Promiscuous Flavin‐dependent Nitroreductase

Abstract: Flavoenzymes are oxidoreductases that catalyze an extensive range of different types of reactions.An advanced and powerful approach to achieving transformations that are normally outside the realm of flavoenzymes is the synergistic combination of photocatalysis and biocatalysis. Here we report the identification of a promiscuous flavin-dependent nitroreductase, BaNTR1, that is able to promote enantioselective photobiocatalytic reductions of a broad range of structurally diverse ketones to yield the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Poelarends demonstrated that similar reactivity could be achieved using nitroreductases, a flavin-dependent oxidoreductase (Figure 45B and C). 137 They found that the nitroreductase from B. amyloliquefaciens could catalyze the reduction of acetophenone and cinnamyl methyl ketone in excellent yield and enantioselectivity. In contrast to the work by Hyster, carbonyl reduction outcompetes alkene reduction for cinnamyl ketones.…”
Section: Flavin-dependent Enzymesmentioning
confidence: 99%
“…Poelarends demonstrated that similar reactivity could be achieved using nitroreductases, a flavin-dependent oxidoreductase (Figure 45B and C). 137 They found that the nitroreductase from B. amyloliquefaciens could catalyze the reduction of acetophenone and cinnamyl methyl ketone in excellent yield and enantioselectivity. In contrast to the work by Hyster, carbonyl reduction outcompetes alkene reduction for cinnamyl ketones.…”
Section: Flavin-dependent Enzymesmentioning
confidence: 99%
“…Gold metalloenzymes have been shown to be interesting and effective in arylation and hydroamination reactions. 27 Indeed, asymmetric reduction of ketones (to synthesize optically pure alcohols) 28 is a crucial step in the synthesis of many pharmaceuticals, agrochemicals, fragrances, and other small organic molecules. 29 In this way, innovative systems such as these newly synthesised gold metalloenzymes, exploiting the biocatalytic environment, the robustness of the enzyme and the efficiency of the gold nanoparticles, have been tested in the asymmetric reduction of acetophenone to 1-phenylethanol (Fig.…”
Section: Paper Nanoscalementioning
confidence: 99%
“…Gold metalloenzymes have been shown to be interesting and effective in arylation and hydroamination reactions. 27 Indeed, asymmetric reduction of ketones (to synthesize optically pure alcohols) 28 is a crucial step in the synthesis of many pharmaceuticals, agrochemicals, fragrances, and other small organic molecules. 29…”
Section: Introductionmentioning
confidence: 99%
“…A common way to obtain enantioenriched alcohols is by the asymmetric reduction of ketones. [21] Thus, new metalloenzymes have been developed in the field of metalloenzyme production.…”
Section: Introductionmentioning
confidence: 99%